Localization of areas of increased vibroactivity by means of the inverse method - STRYCZNIEWICZ, Lesław (Archives of Acoustics, 2007)
Increased possibilities of parallel acquiring data and transforming them effectively together with the improvement of calculation tools made the inverse methods more important. Some examples of research, carried out by the author, during, which the possibilities of localization of increased vibroactivity areas were studied using the multi-microphone method, are presented in the paper. The theoretical basis of the inversion method of sound sources localization and certain laboratory test results are also given.